Beyond boundaries: a location-based toolkit for quantifying group dynamics in diverse contexts. - Elkin-Frankston, Seth.; McIntyre, James.; Brunyé, Tad T; Gardony, Aaron L; Hancock, Clifford L; O'Donovan, Meghan P; Bode, Victoria G; Miller, Eric L (Tufts University. Tisch Library., 2025)
Springer Open.